SYNTHESIS AND CHARACTERIZATION OF SnO2 USING JAPANESE PAPAYA LEAF EXTRACT (Cnidoscolus aconitifolius) AS CAPPING AGENT BY HYDROTHERMAL METHOD - Amanta, Reyrin Ceria; Nadia Refa Fheronica; Asdim; Banon, Charles; Irfan Gustian; Eka Angasa (UIN Mataram, 2023)
Synthesis of SnO2 has been carried out by using extract of Cnidoscolus aconitifolius leaf as a natural capping agent. The synthesis aims to determine the effect of the use of a capping agent on the crystallinity and the size of crystals. The mass variations of the capping agent used were 5, 10, and 15 gram using the hydrothermal method at relatively low temperature (95-100°C). The synthesized of SnO2 were characterized using FTIR (Fourier Transform Infra Red Spectroscopy) and XRD (X-Ray Difraction). The results of FTIR characterization show the stretching vibration absorption band of Sn-O-Sn in the spectrum with and without capping agent at wave number 599 cm-1 and 599.333 cm-1 . XRD diffractogram shows that SnO2 without a capping agent and using a capping agent has relatively the same crystallinity. Mass variations of 5, 10, and 15 gram resulted in crystals measuring 14.37 nm, 13.75 nm, and 11.78 nm and SnO2 without capping agent measuring 15.93 nm. The results showed that the Cnidoscolus aconitifolius leaf solution could be used as a natural capping agent to produce SnO2. The results of SEM characterization show that aggregate reduction can be seen in the addition of Japanese papaya (Cnodoscolus aconitifolius) capping agent.